Analisis Kinerja Lembaga Penyelenggara Pelayanan Sosial dalam Pembinaan Anak Penyandang Tunagrahita Terlantar di Kampung Anak Negeri Kota Surabaya - Nassa Yulinda Sari; Sri Wahyuni (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2023)
The Surabaya City Government through the Social Service, formed the UPTD Kampung Anak Negeri, listed in Surabaya Mayor Regulation Number 119 of 2021 concerning the Formation and Organizational Structure of the Technical Implementation Unit for the Kampung Anak Negeri Service at the Surabaya City Social Service. The aim of the study was to analyze and find out the supporting and inhibiting factors for the performance of social service delivery institutions in fostering abandoned mentally retarded children at UPTD Kampung Anak Negeri Surabaya City. The method used is a qualitative method with a descriptive approach. Data collection techniques using observation, interviews and documentation. Theory uses guidelines in compiling performance reports, State Administration Institutions (LAN, 2018). The results of the research show that the (input) is adequate in terms of human resource needs, sources of budget allocations and policies or Standard Operating Procedures, but in ideal ratio, comparisons do not yet have a reference. (output) is already visible in the provision of skills. (outcome) has fulfilled physical and non-physical needs, but education has not been given and there is an increase in potential with the work of neglected mentally retarded children. (benefits) realizing independence in daily activities and long-term benefits, that is, if a mentally retarded child still has a family, they will be sent home. (positive impact) can be seen that there is an increase in enthusiasm for learning for neglected children with mental retardation, while the negative impact is that there are abandoned children with mental retardation who do not want to be reunified with their family.